Thomas More in the Virorum doctorum de disciplinis benemerentium effigies XLIIII (1572) - Olivares-Merino, Eugenio M. (International Journal of English Studies, 2024)
While in Antwerp to work on his edition of the Polyglot Bible (1573), the Spanish humanist Benito Arias Montano met the Dutch engraver, Philip Galle. They collaborated on the publication of the Virorum doctorum de disciplinis benemerentium effigies XLIIII (1572), a collection of over 40 portraits, each accompanied by a Latin epigram by the Spaniard. One of these portraits corresponds to Thomas More; and it was the first time that an engraving of Henry VIII’s Chancellor appeared in a portrait book. This study analyzes More’s presence in Galle’s and Arias Montano’s volume. After dealing with the sources of Galle’s graphic representation of More and its formal analysis, we clarify why the Spanish Netherlands were a most fitting context for the popularisation of More’s image in printed works. The Spaniard’s possible role in the creation of the final list of 44 illustrious men is also relevant, though it has primarily been argued by Spanish scholars. Other aspects related to the genesis of the Virorum doctorum are also taken into account before concluding with an analysis of the two versions of the Latin epigram that Arias Montano composed for More, a synthesis of what the Spaniard admired in the ill-fated English author.